2015
DOI: 10.1094/mpmi-12-14-0411-r
|View full text |Cite
|
Sign up to set email alerts
|

The VELVET Complex in the Gray Mold FungusBotrytis cinerea: Impact of BcLAE1 on Differentiation, Secondary Metabolism, and Virulence

Abstract: Botrytis cinerea, the gray mold fungus, is an important plant pathogen. Field populations are characterized by variability with regard to morphology, the mode of reproduction (conidiation or sclerotia formation), the spectrum of secondary metabolites (SM), and virulence. Natural variation in bcvel1 encoding the ortholog of Aspergillus nidulans VeA, a member of the VELVET complex, was previously shown to affect light-dependent differentiation, the formation of oxalic acid (OA), and virulence. To gain broader in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 76 publications
6
88
0
Order By: Relevance
“…This suggests that this collection of B. cinerea genotypes does not contain large-effect qualitative virulence loci; instead, this generalist uses a highly polygenic virulence architecture (Denby et al, 2004;Finkers et al, 2007b;Rowe and Kliebenstein, 2008;Corwin et al, 2016b;Zhang et al, 2016). This agrees with previous B. cinerea mechanistic studies that identify a large collection of standing genetic variation that controls a wide range of specific virulence mechanisms (Choquer et al, 2007;Rowe and Kliebenstein, 2007;Noda et al, 2010;Rowe et al, 2010;Dalmais et al, 2011;Michielse et al, 2011;Shlezinger et al, 2011;Windram et al, 2012;Pearson and Bailey, 2013;Kumari et al, 2014;An et al, 2015;Atwell et al, 2015;Hevia et al, 2015;Plaza et al, 2015;Schumacher et al, 2015;Zhang et al, 2015a;Corwin et al, 2016aCorwin et al, , 2016bLopezCruz et al, 2017;Zhang et al, 2016). Taken together, this supports the perspective that the Arabidopsis-B.…”
Section: Natural Genetic Variation In B Cinerea Influences Plant Trasupporting
confidence: 83%
See 1 more Smart Citation
“…This suggests that this collection of B. cinerea genotypes does not contain large-effect qualitative virulence loci; instead, this generalist uses a highly polygenic virulence architecture (Denby et al, 2004;Finkers et al, 2007b;Rowe and Kliebenstein, 2008;Corwin et al, 2016b;Zhang et al, 2016). This agrees with previous B. cinerea mechanistic studies that identify a large collection of standing genetic variation that controls a wide range of specific virulence mechanisms (Choquer et al, 2007;Rowe and Kliebenstein, 2007;Noda et al, 2010;Rowe et al, 2010;Dalmais et al, 2011;Michielse et al, 2011;Shlezinger et al, 2011;Windram et al, 2012;Pearson and Bailey, 2013;Kumari et al, 2014;An et al, 2015;Atwell et al, 2015;Hevia et al, 2015;Plaza et al, 2015;Schumacher et al, 2015;Zhang et al, 2015a;Corwin et al, 2016aCorwin et al, , 2016bLopezCruz et al, 2017;Zhang et al, 2016). Taken together, this supports the perspective that the Arabidopsis-B.…”
Section: Natural Genetic Variation In B Cinerea Influences Plant Trasupporting
confidence: 83%
“…Additionally, B. cinerea is a true haploid ascomycete that infects a wide range of evolutionarily distinct plant hosts, from bryophytes to eudicots. B. cinerea has elevated natural genetic variation that results in multiple major-effect polymorphisms in known virulence mechanisms, including the production of phytotoxic metabolites (Colmenares et al, 2002;Dalmais et al, 2011), enzymes that detoxify plant defense metabolites (Ferrari et al, 2003;Pedras et al, 2005Pedras et al, , 2007Pedras et al, , 2008Pedras et al, , 2009Pedras et al, , 2011Stefanato et al, 2009;Rowe et al, 2010), and the ability to degrade plant cell walls (Rowe and Kliebenstein, 2007;Schumacher et al, 2012Schumacher et al, , 2015Kumari et al, 2014). Because wild B. cinerea isolates have recombination and random mating, a population of isolates is a random intermixed sample of the diverse virulence mechanisms (Rowe and Kliebenstein, 2007;Kretschmer et al, 2009;Rowe et al, 2010;Kumari et al, 2014;Atwell et al, 2015;Corwin et al, 2016aCorwin et al, , 2016bZhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As the mycelium of the mutant looked paler than that of the WT, pigmentation defects of the bcskn7 mutant were assumed. Therefore, the expression of genes involved in melanin biosynthesis (bcpks13 and bcscd1) was examined (50,51). The strains were grown for 4 days in constant light (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, this data indicates that the response of A. niger to GT is very similar to the response under carbon starvation and suggests that GT causes a nutrient requirement which leads to the production of hydrolytic enzymes. Relevantly, it has been observed that the production of CAZymes and proteases depends on functional regulators BcVEL1 and BcLAE1, in Botrytis cinerea, which are the A. nidulans orthologs of VeA and the SAM-dependent methyltransferase LaeA, respectively [55]. In A. nidulans, VeA and LaeA form a trimeric complex with another member of the velvet protein family, VelB, and this complex is responsible for the regulation of secondary metabolism and development [56].…”
Section: Discussionmentioning
confidence: 99%